Uniformly convergence of the spectral expansions of the schrödinger operator on a closed domain - Ahmedov, Anvarjon A.; Jamaludin, Nur Amalina; Rakhimov, Abdumalik (Institute of Physics Publishing, 2013)
In this work uniformly convergent problems of the eigenfunction expansions of the SchrÄodinger operator ¡¢+q(y1; y2) with singular potential from W1 2 () are investigated. Using the estimation of the spectral function of the SchrÄodinger operator on closed domain and mean value formula for the eigenfunction the uniformly convergent of the eigenfunction expansions of the functions continuous on the closed domain is proved.